Increased Atmospheric CO 2 Adversely Affects Large Pollinators, but Benefits Small Pollinators - Shahmshad Ahmed Khan; Muhammad Tanveer; Kit Prendergast; Taimoor Hussain; Arslan Shehryar; Asif Mehmood (Global Ecology and Biogeography, 2026)
Aim This study examines the impact of atmospheric CO 2 concentration on pollinator communities, focusing on body size‐related responses. It aims to understand how natural CO 2 variability influences pollinator abundance and diversity, and to assess potential ecological consequences for pollination services and ecosystem stability. Location The study was conducted across the Pothwar Plateau in Punjab, Pakistan, covering five districts: Murree, Rawalpindi/Islamabad, Jhelum, Chakwal and Attock. Time Period Field data were collected from September 2018 to May 2022, excluding December and January when pollinator activity was low. Major Taxa Studied The study focused on insect pollinators, including bees and hoverflies, and classified them into large‐ and small‐bodied groups based on size thresholds (e.g., bees were classified as large if their body length was ≥ 15 mm, and flies were classified as large if their body length was ≥ 10 mm). Methods A total of 25 study sites were randomly selected across an elevational gradient ranging from 350 to 2291 m. Atmospheric CO 2 concentrations were measured using a Temtop M2000 2nd digital meter at a standardized height of 1 m. Pollinator abundance and diversity were monitored using a transect‐based observation method (50 m transects, four per site). Sampling was conducted weekly from September to May, excluding December and January. Pollinators were identified in the field or collected for species‐level identification in the laboratory using morphological and image‐based techniques. Body size was measured using digital callipers. Statistical analyses were performed using Generalized Linear Mixed Models (GLMMs) to evaluate the relationship between pollinator populations, atmospheric CO 2 levels and other abiotic factors, while accounting for body size. Results A significant size‐dependent response to atmospheric CO 2 concentrations was observed. Larger‐bodied pollinators showed declines in abundance and diversity with increasing CO 2 levels, likely due to higher metabolic oxygen demands. In contrast, smaller‐bodied pollinators showed a positive association with elevated CO 2 concentrations. The relationship between CO 2 and pollinator communities remained consistent across different sites, confirming CO 2 as a reliable predictor variable. Main Conclusions Rising atmospheric CO 2 concentration could restructure pollinator communities by favouring smaller‐bodied species while negatively affecting larger‐bodied pollinators. This shift may have cascading effects on pollination networks and ecosystem stability. Conservation strategies should account for size‐specific vulnerabilities to climate‐induced CO 2 changes and prioritize protecting larger‐bodied pollinators, as they are more susceptible to CO 2 ‐related declines.